THE EFFECT OF REWARD AND PUNISHMENT METHODS ON LEARNING OUTCOMES OF IPS IN CLASS IV STUDENTS - Dina Anika Marhayani; Sinta Sinta; Evinna Cinda Hendriana; Park Haewoon; Zheng Canghong (Journal of Educational Review and Research, 2023)
This study aims to: 1) determine differences in social studies learning outcomes between classes given the reward and punishment method and conventional classes in fourth grade students at SDN 23 Singkawang; 2) find out how much influence the reward and punishment method has on social studies learning outcomes in fourth grade students at SDN 23 Singkawang. The type of research used is quasi- experimental quantitative research (quasi experimental design) with a Nonequivalent control group design with the form of experimental class and control class. The sampling technique used purposive sampling was selected for the experimental class, namely class IV B and control class, class IV A. The experimental class was treated using the reward and punishment method, while the control class was not treated using conventional learning. The data analysis technique used in this study is the two sample t test and the effect size formula. The results showed (1) there was an influence between classes using the reward and punishment method and classes using conventional learning, seen from the calculation of the post-test learning outcomes of the experimental class and the control class using the two- sample T test showed that tcount = 2.368 > ttable = 2.0048 with a significance level of 5%, meaning that Ha is accepted and Ho is accepted rejected; (2) the reward and punishment learning method has a high effect on student social studies learning outcomes by using the effect size formula with a value of 1.104.